Bigo[ng bayani] si Tatay representations of the overseas Filipino worker in Philippine commercials - Luna, Bianca Camille P.; Guieb, Eulalio III, R.; University of the Philippines. College of Mass Communication (2013)
"This study is about the representation of overseas Filipino workers (OFWs) in commercials. It provides a classification of the themes of being an OFW as represented in commercials. It also seeks to identify how I see my father who is an OFW in the representations portrayed. I employ the theory of representation and semiotics in order to determine these portrayals. The analysis dwells on three levels: (1) the characterization of the OFW in each commercial, (2) the actual narrative, and (3) the technical aspects (e.g., images, scoring) of each advertisement. These representations of the OFW are classified into the following themes: the laborer OFW, the absent OFW, the stranger OFW, and the bagong bayani. To provide a more in-depth discussion of the representations identified, an ethnographic analysis is employed. A personal narrative of my father through my perspective is provided by juxtaposing my point of view as a daughter of an OFW vis-a-vis the OFW representations in the commercials. This thesis intents to make people aware of the conditions of an OFW through my experience as a daughter of one, and not just by the representations portrayed in the commercials."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Filipinos -- Employment in foreign countries; Foreign workers -- On television; Television commercials -- Philippines